Penerapan Terapi Thought Stopping untuk Menurunkan Kecemasan pada Klien Hipertensi - Deborah Ferdinanda Lumenta; Novy Helena Catharina Daulima; Herni Susanti; Ice Yulia Wardani (Jurnal Keperawatan Silampari, 2022)
This study aims to provide an overview of the application of TS to Hypertension clients described in the form of case reports. The research method used in this study is a case report. The results showed that after applying Thought Stopping (TS) for three sessions, there was a decrease in signs and symptoms of anxiety. In conclusion, Thought Stopping therapy can reduce stress, especially disturbing thoughts in Hypertensive clients. Keywords: Hypertension, Anxiety, Thought Stopping